2006
DOI: 10.1007/s00436-006-0145-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of gastrointestinal helminths in chicken farms in the Gharb region—Morocco

Abstract: Gastrointestinal tracts of 300 chickens from three villages of the Gharb region, Morocco, were examined for adult helminths during 2002-2005. Helminth species found were: Notocotylus gallinarum (prevalence 0.7%), Hymenolepis carioca (3.7%), Raillietina echinobothrida (5.7%), Hymenolepis contaniana (7%), Raillietina tretragona (9.3%), Raillietina cesticillus (12%), Capillaria obsignata (6%), Subulura brumpti (15.3%), Heterakis gallinarum (10%), Cheilospirura hamulosa (2.7%), Dispharynx nasuta (5.3%), Ascaridia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
3
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 8 publications
(5 reference statements)
5
16
3
3
Order By: Relevance
“…We found no significant difference in prevalence of parasitic infection in terms of sex of the host, and this results corresponds well with the findings of (Hassouni and Belghyti 2006;Poulsen et al 2000) who also documented similar prevalence of helminth infection irrespective of the sex.…”
Section: Discussionsupporting
confidence: 92%
“…We found no significant difference in prevalence of parasitic infection in terms of sex of the host, and this results corresponds well with the findings of (Hassouni and Belghyti 2006;Poulsen et al 2000) who also documented similar prevalence of helminth infection irrespective of the sex.…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with the Katoch et al 2012;Saad et al (1989) and Puttalakshmamma et al (2008), who reported 72.0, 77.3 and 71 % helminthic infections in local chickens, respectively. The higher prevalence of helminthic infections in local chickens was reported from other countries includes Morocco, 89.9 % (Hassouni and Belghyti 2006);Nigeria, 87.7 % (Yorio et al 2008) and Iran, 96 % (Eslami et al 2009). The difference might be due to variation in the type of managemental practices adopted, geographical locations and the number of samples included in the study.…”
Section: Resultsmentioning
confidence: 87%
“…However, large numbers can have a devastating effect on growth, egg production, and over-all health. Parasitism has been attributed to causes of reduced growth, egg production, emaciation, and anaemia as well as mortality (Belonwu, 1993;Hassouini and Belghyti, 2006;Heyradin et al, 2012). These authors reported that mortality due to parasitic diseases was higher than those attributed to Newcastle disease and mortality causing viral infection of poultry.…”
Section: Introductionmentioning
confidence: 99%